Der Erste Weltkrieg im Spiegel nationalen Gedenkens – Die drei Soldatenfriedhöfe auf dem Südwestkirchhof Stahnsdorf bei Berlin - Ladegast, Anett (RIHA Journal, 2017)
In a unique constellation, and in immediate proximity to one another, the Südwestkirchhof in Stahnsdorf near Berlin comprises three World War I military cemeteries: A German, a British, and an Italian one. The article not only compares the design of the three cemeteries, but also the alterations across the decades following the war; especially World War II and the period of the Division of Germany brought about substantial changes to these sites. By analyzing the handling of the often very practical problems of maintenance and attendance of these diplomatically highly sensible memorial sites, they emerge as indicators of changes in international relationships and national remembrance politics.